The Effectiveness of Celery Leaf (Apium Graveolens L) Decoction in Reducing Hypertension in Menopause at PMB Bidan A Campaka, Purwakarta Regency - Bunga Anggita Sagia; Santi Sulistiawati (Riviera Publishing, 2025)
Menopause is experienced by many people who suffer from hypertension, but many ignore it without taking proper treatment. If not treated immediately, complications may occur. To address this, one non-pharmacological alternative is herbal therapy. Celery leaf herbal therapy can reduce the kidneys' function in increasing blood pressure, so it can be used to treat hypertension in menopause. The research aims to determine the effect of the effectiveness of celery leaf (Apium graveolens L) decoction on reducing hypertension in menopause. This study used a quasi-experimental design with one group pretest and posttest without a control group. The sample consisted of menopausal women suffering from hypertension, totaling 30 respondents. The sample was selected using purposive sampling, and the measurement tools included questionnaires, interviews, and observations. The results showed that menopausal women who did not consume celery leaf decoction had an average value of 0.47, while those who consumed it had an average value of 0.76. The statistical test used was the non-parametric Mann-Whitney test, which yielded a significance value of P = 0.000 (<0.005), indicating a significant difference between those given and not given celery leaf decoction.